The role of PAK1 in the sensitivity of kidney epithelial cells to ischemia-like conditions. Issue 5 (4th March 2019) - Zynda, Evan R.; Maloy, Mitchell H.; Kandel, Eugene S.
ABSTRACT: Kidney ischemia, characterized by insufficient supply of oxygen and nutrients to renal epithelial cells, is the main cause of acute kidney injury and an important contributor to mortality world-wide. Earlier research implicated a G-protein coupled receptor (NK1R) in the death of kidney epithelial cells in ischemia-like conditions. P21-associated kinase 1 (PAK1) is involved in signalling by several G-proteins. We explored the consequences of PAK1 inhibition for cell survival under the conditions of reduced glucose and oxygen. Inhibition of PAK1 by RNA interference, expression of a dominant-negative mutant or treatment with small molecule inhibitors greatly reduced the death of cultured kidney epithelial cells. Similar protection was achieved by treating the cells with inhibitors of MEK1, in agreement with the prior reports on PAK1-MEK1 connection. Concomitant inhibition of NK1R and PAK1 offered no better protection than inhibition of NK1R alone, consistent with the two proteins being members of the same pathway. Furthermore, NK1R, PAK and MEK inhibitors reduced the induction of TRAIL in ischemia-like conditions. Considering the emerging role of TRAIL in ischemia-mediated cell death, this phenomenon may contribute to the protective effects of these small molecules. Our findings support further exploration of PAK and MEK inhibitors as possible agents to avert ischemic kidney injury.